Microfluidic qPCR for Microbial Ecotoxicology in Soil: A Pilot Study - Crane, Sally (UNSW Sydney, 2016)
From the late 1990’s there have been numerous calls to increase the biological relevance of methods used in ecotoxicology, by including environmental variation in experimental designs and replacing single-species tests with community-wide assessments. Quantitative PCR (qPCR) allows researchers to assess the impact of contamination on microbial communities involved in key processes such as nitrogen cycling, but is labor intensive, costly and requires a high degree of operator skill. Investigations are therefore usually restricted to quantifying 3 - 4 genes. Here we present the first application of microfluidic qPCR (MFQPCR) to microbial processes in soil. Utilising existing primer sets, we developed a MFQPCR assay for soil hydrocarbon ecotoxicology targeting the nitrogen cycle, hydrocarbon degradation and taxa, including bacteria and fungi. With as little as 6.7 nl reaction volumes, each chip has the capacity to quantify 14 genes across 30 samples in less than 5 hours, with costs per reaction less than half that of traditional qPCR. We developed the FuelTox pipeline, combining our MFQPCR assay with long-term in-situ mesocosms (114 weeks), fingerprinting (ARISA), factor-qPCR and multi-variate analysis, to assess the ecotoxicology of residual hydrocarbons on soil microbes on sub-Antarctic Macquarie Island. Principal response curves (PRC) of MFQPCR-derived gene abundances revealed significant inhibition of the endemic microbial community in response to fuel spiking; with bacterial laccase-like and denitrification (nosZ, nirK & narG) genes the most sensitive. Unlike previous Macquarie Island studies with fresh fuel, we observed similar sensitivities over our entire spiking range of 50 – 10 000 mg/kg, with no stimulation of nosZ, alkB or nah genes, commonly associated with hydrocarbon degradation observed. By 69 weeks post-spiking we observed significant reductions in spiking compounds (54-99%) and most significantly the recovery of the microbial community to that prior to fuel spiking. This study demonstrates that MFQPCR is not only a fast and cost-effective alternative to traditional qPCR, but it can be used for multi-variate analysis, thereby producing results that are directly comparable with more traditional ecotoxicology studies, such as single species tests using invertebrates or larger organisms. Due to the flexibility of MFQPCR, the FuelTox pipeline has great potential to be adapted to assess other contaminants and environmental stressors, by simply interchanging the primer sets used to target alternative genes of interest.